Effective Professional Development on Teaching at Islamic Boarding School: English Teachers’ Perspective - Humaeroah (LETS: Journal of Linguistics and English Teaching Studies, 2023)
The objectives of the research are to find out (1) English teachers’ perspective towards the criteria of effective teacher’s professional development activities, (2) professional development needs on teaching in Islamic Boarding School, and (3) English teachers’ barriers to participate teacher professional development activities. This study was designed as descriptive qualitative research. The subject of data in this research was English teacher in Islamic Boarding School. This research took ten English teachers as the participants of the research which is collected through purposive sampling. Data collection techniques used were interview and observation checklist. The results of the study indicated that (1) there were five criteria of effective professional development activity mentioned by the teachers in Islamic Boarding School. Those were a match to existing teacher needs, teacher involvement in the design/planning of professional development activity, active participation oppurtunities, long-term engagement, and high quality instructor. (2) It was also found six features the teacher perceived as professional development needs by the teachers. Those were content and performance standards, clasroom management, Intructional practice, ICT teaching skills, and student discipline and behaviour problem. (3) There were three barriers which fit the existing features, those were no suitable development, conflict with work schedule, family responsibilities, negative attitudes towards courses, and health problem. Besides that, the researcher also found three kinds of barrier that was not fit with the existing barriers, those are transportation problem, unavoidable condition, and unreachable information. Then, two participants expressed that they did not have any barrier to participate in professional development activities